2016
DOI: 10.1016/j.bpj.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among DNA Linker Length, Linker Histone Concentration, and Histone Tails in Chromatin

Abstract: Eukaryotic cells condense their genetic material in the nucleus in the form of chromatin, a macromolecular complex made of DNA and multiple proteins. The structure of chromatin is intimately connected to the regulation of all eukaryotic organisms, from amoebas to humans, but its organization remains largely unknown. The nucleosome repeat length (NRL) and the concentration of linker histones (ρLH) are two structural parameters that vary among cell types and cell cycles; the NRL is the number of DNA basepairs wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…43 The contrasting influence of linker histone isoforms on the chromatosome structure and energetics, and the extent to which they affect greater chromatin dynamics, remains unclear. [44][45][46] Using Brownian dynamic docking simulations, Öztürk et al found that GH5 displays a range of conformational flexibility and affects the overall chromatosome dynamics, including the linker DNA. 47 With similar techniques they later showed that even slightly varied linker histone sequences, including point mutations and posttranslational modifications, can significantly affect the chromatosome structure.…”
Section: Introductionmentioning
confidence: 99%
“…43 The contrasting influence of linker histone isoforms on the chromatosome structure and energetics, and the extent to which they affect greater chromatin dynamics, remains unclear. [44][45][46] Using Brownian dynamic docking simulations, Öztürk et al found that GH5 displays a range of conformational flexibility and affects the overall chromatosome dynamics, including the linker DNA. 47 With similar techniques they later showed that even slightly varied linker histone sequences, including point mutations and posttranslational modifications, can significantly affect the chromatosome structure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the LH type we follow (rat H1) is also longer by about 20 amino acids that the H1ºa system used by Fang et al 24 . Nevertheless, prior studies in agreement with a large array of experimental data 25, 26, 27, 29, 30, 28, 31, 32, 33, 34 suggest that in-silico studies help shed light on chromatin structure and energy trends, especially when conducted on a large set of system 25, 26, 27, 29, 30, 28, 31, 32, 33, 34 s with systematic parameters variations. Future models that allow DNA unwrapping, dynamic LH binding/unbinding, and other linker histone species can address these limitations.…”
Section: Resultsmentioning
confidence: 87%
“…For long linkers, the excess linker DNA forms other interactions with the tails and neighboring units, promoting bending and polymorphic states 32 . Previous work has also examined the LH-dependent fiber condensation 30, 31, 33 , and the synergistic folding of the LH and the chromatin fiber 25, 34 . LH condenses synergistically as the chromatin fiber forms a compact zigzag structure, and its LH condensation depends sensitively on the salt environment.…”
Section: Introductionmentioning
confidence: 99%
“…This fits nicely with evidence that the cell may also actively regulate linker length in response to linker histone binding, which also varies across cell cycle stage. 67 …”
Section: Discussionmentioning
confidence: 99%